Age-Related Morpho functional Features of Changes in the Thymus of Experimental Animals Under the Action of Asd-2 - Asadova Nigora Khamroyevna; Teshaev Shukhrat Zhumaevich (Zien Journals, 2023)
The study of the literature has shown that the morphological status of the thymus has been studied superficially in many works. The cellular composition of the thymus parts under the influence of physical or chemical environmental factors in the age aspect has not been studied enough. All this requires a more detailed study of the morphological changes occurring in this organ under the influence of various factors
Keywords: thymus; T-lymphocyte; ASD-2 fraction